Jackson Pollock - Toynton, Evelyn, 1950- (Icons of America., 2012)
Jackson Pollock (1912-1956) not only put American art on the map with his famous "drip paintings," he also served as an inspiration for the character of Stanley Kowalski in Tennessee Williams's A Streetcar Named Desire -the role that made Marlon Brando famous. Like Brando, Pollock became an icon of rebellion in 1950s America, and the brooding, defiant persona captured in photographs of the artist contributed to his celebrity almost as much as his notorious paintings did. In the years since his death in a drunken car crash, Pollock's hold on the public imagination has only increased. He has become an enduring symbol of the tormented artist-our American van Gogh. In this highly engaging book, Evelyn Toynton examines Pollock's itinerant and poverty-stricken childhood in the West, his encounters with contemporary art in Depression-era New York, and his years in the run-down Long Island fishing village that, ironically, was transformed into a fashionable resort by his presence. Placing the artist in the context of his time, Toynton also illuminates the fierce controversies that swirled around his work and that continue to do so. Pollock's paintings captured the sense of freedom and infinite possibility unique to the American experience, and his life was both an American rags-to-riches story and a darker tale of the price paid for celebrity, American style.